2022
DOI: 10.1002/ncp.10922
|View full text |Cite
|
Sign up to set email alerts
|

Early vs late enteral nutrition in pediatric intensive care unit: Barriers, benefits, and complications

Abstract: Background: This study aimed to define the existing barriers for early enteral nutrition (EEN) in critically ill children and to analyze the differences in nutrient supply, complications, and outcomes between EEN and late EN (LEN). Methods: This is a secondary analysis of a multicenter observational, prospective study including critically ill children receiving EN. Variables analyzed included demographic and anthropometric features, caloric and nutrient supply, outcomes, and complications according to the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Early initiation of EN may result in quicker achievement of higher energy intakes during pediatric critical illness. In an additional secondary analysis of a multicenter observational study including 68 infants and children from 12 PICUs in Spain, EN started within 48 h vs after 48 h was associated with significantly higher energy intake and faster attainment of maximum energy provision, 8 guided by the Schofield equation. 19 With EN initiated in 24 h compared with after 24 h, a significantly shorter duration of mechanical ventilation was revealed, although severity of illness was significantly and positively correlated with the timing of EN initiation.…”
Section: Timing Of En Initiationmentioning
confidence: 99%
See 3 more Smart Citations
“…Early initiation of EN may result in quicker achievement of higher energy intakes during pediatric critical illness. In an additional secondary analysis of a multicenter observational study including 68 infants and children from 12 PICUs in Spain, EN started within 48 h vs after 48 h was associated with significantly higher energy intake and faster attainment of maximum energy provision, 8 guided by the Schofield equation. 19 With EN initiated in 24 h compared with after 24 h, a significantly shorter duration of mechanical ventilation was revealed, although severity of illness was significantly and positively correlated with the timing of EN initiation.…”
Section: Timing Of En Initiationmentioning
confidence: 99%
“…Despite uncommon reports of adverse events, early EN in 24–48 h from admission or injury is safe and tolerable for the majority of children with critical illness. Early EN improves gastrointestinal tolerance in some patients, with reports of decreased constipation 8 and reduced abdominal distension 17 . Results of these observational studies are confounded by the inability to control for all variables impacting study outcomes, and more randomized controlled trials are needed to determine safety, tolerance, and efficacy of early vs delayed EN.…”
Section: Timing Of En Initiationmentioning
confidence: 99%
See 2 more Smart Citations
“…EEN has also been associated with a reduction in mortality, length of hospital stays and weight loss when compared to DEN [ 13 ]. A recent multicenter study in critically ill children also found that early enteral nutrition could be helpful in improving nutrient delivery, reducing time on mechanical ventilation and preventing constipation in sick children [ 14 ]; however, the presence of cardiac disease, mechanical ventilation and an age of over 12 months were risk factors associated with DEN. International guidelines recommend early enteral nutrition in critically ill children with hemodynamic support, extracorporeal life support and other situations once the child has been resuscitated [ 6 , 15 ], but enteral nutrition is often delayed due to gastrointestinal intolerance or the need to restrict fluid intake, making critically ill children prone to receiving insufficient calorie and protein intake [ 16 ].…”
Section: Introductionmentioning
confidence: 99%